Prevention of Delayed Graft Function in Kidney Transplant Recipients through a Continuous Infusion of the Prostaglandin Analogue Iloprost: A Single-Center Prospective Study - Massimiliano Veroux; Floriana Sanfilippo; Giuseppe Roscitano; Martina Giambra; Alessia Giaquinta; Giordana Riccioli; Domenico Zerbo; Daniela Corona; Massimiliano Sorbello; Pierfrancesco Veroux (Biomedicines, 2024)
Background: Delayed graft function (DGF) is common after kidney transplantation from deceased donors and may significantly affect post-transplant outcomes. This study aimed to evaluate whether an innovative approach, based on the administration of the intravenous prostaglandin analogue iloprost, could be beneficial in reducing the incidence of DGF occurring after kidney transplantation from deceased donors. Methods: This prospective, randomized (1:1), placebo-controlled study enrolled all consecutive patients who received a kidney transplant from a deceased donor from January 2000 to December 2012 and who were treated in the peri-transplant period with the prostaglandin analogue iloprost at 0.27 μg/min through an elastomeric pump (treatment group) or with a placebo (control group). Results: A total of 476 patients were included: DGF was reported in 172 (36.1%) patients in the entire cohort. The multivariate analysis showed that the donor’s age > 70 years (OR 2.50, 95% confidence interval (CI): 1.40–3.05, p < 0.001), cold ischemia time > 24 h (OR 2.60, 95% CI: 1.50–4.51, p < 0.001), the donor’s acute kidney injury (OR 2.71, 95% CI: 1.61–4.52, p = 0.021) and, above all, the recipient’s arterial hypotension (OR 5.06, 95% CI: 2.52–10.1, p < 0.0001) were the strongest risk factors for developing post-transplant DGF. The incidence of DGF was 21.4% in the treatment group and 50.9% in the control group (p < 0.001). Interestingly, among patients who developed DGF, those who received iloprost had a shorter duration of post-transplant DGF (10.5 ± 8.3 vs. 13.4 ± 6.7, days, p = 0.016). Conclusions: This study showed that the use of a continuous infusion of iloprost could safely and effectively reduce the incidence of DGF in recipients of deceased-donor kidneys, allowing a better graft functionality as well as a better graft survival.